Pemetaan Gaya Dan Tipe Kepemimpinan Kepala Sekolah - Sunarni (Universitas Negeri Malang, 2018)
Abstract: The purpose of this research is to know style, type, leadership style, and leadership type that most dominant of headmasters of state primary schools, state junior and senior high school in Malang City. Quantitative approach with descriptive exploratory analysis design. Population (136) headmasters of state primary schools, state junior and senior high school in Malang City, sample of random sampling 41 people. Data collection techniques use questionnaire, factor analysis and descriptive. Outcome: (1) 5 types of leadership style, that is democratic, delegative, militaristic/autocratic, exploitative, and consultative, (2) leadership type that is administrative/executive, democratic, populist/nationalistic, charismatic and authoritarian/autocratic, (3) the most dominant democratic style the headmaster answered agree, the delegative style and consultative answer agreed, militaristic/autocratic style and exploitative less agree. (4) administrative/executive type, democratic, charismatic, and authoritarian, the most dominant principal responds agree, and populist/nationalistic type responds less agree. Abstrak: Tujuan penelitian mengetahui gaya, tipe, gaya kepemimpinan paling dominan, dan tipe kepemimpinan paling dominan kepala sekolah SD, SMP, dan SMA Negeri Kota Malang. Pendekatan kuantitatif dengan rancangan analisis deskriptif eksploratori. Populasi (136) orang kepala SD, SMP, dan SMA Negeri se-Kota Malang, sampel random sampling 41 orang. Teknik pengumpulan data angket, analisis faktor dan deskriptif. Hasil: (1) gaya kepemimpinan ada 5 macam yaitu demokratik, delegatif, militeristik/otokratis, eksploitatif, dan konsultatif, (2) tipe kepemimpinan yaitu administratif/eksekutif, demokratis, populistik/nasionalistik, karismatik, dan otoriter/otokratis, (3) gaya demokratik paling dominan kepala sekolah menjawab setuju, gaya delegatif dan konsultatif menjawab setuju, gaya militeristik/otokratis) dan eksploitatif kurang setuju, (4) tipe administrative/eksekutif), demokratik, karismatik, dan otoriter yang paling dominan kepala sekolah menjawab setuju, dan tipe populistik/nasionalistik) menjawab kurang setuju.